2015
DOI: 10.3389/fphys.2015.00359
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Matrix Stiffness and c-SRC in Hepatic Fibrosis

Abstract: Introduction: In liver fibrosis activation of hepatic stellate cells (HSC) comprises phenotypical change into profibrotic and myofibroplastic cells with increased contraction and secretion of extracellular matrix (ECM) proteins. The small GTPase RhoA orchestrates cytoskeleton formation, migration, and mobility via non-receptor tyrosine-protein kinase c-SRC (cellular sarcoma) in different cells. Furthermore, RhoA and its downstream effector Rho-kinase also play a crucial role in hepatic stellate cells and hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 41 publications
(58 reference statements)
2
28
1
1
Order By: Relevance
“…However, few studies have investigated the role of Src in liver fibrosis. A recent report showed that phosphorylation of Src at Y416 and Y530 is decreased and increased during liver fibrosis, respectively [12]. However, the current study demonstrated that phosphorylation of Src at Y416 was increased during the activation of primary HSCs and in liver tissues of TAA-injected mice.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…However, few studies have investigated the role of Src in liver fibrosis. A recent report showed that phosphorylation of Src at Y416 and Y530 is decreased and increased during liver fibrosis, respectively [12]. However, the current study demonstrated that phosphorylation of Src at Y416 was increased during the activation of primary HSCs and in liver tissues of TAA-injected mice.…”
Section: Discussioncontrasting
confidence: 71%
“…Src was originally identified as an oncogene and it is expressed in human tumors; however, it is also ubiquitously expressed in all cell types. Src phosphorylates the signaling proteins STAT3, AKT, and epidermal growth factor receptor (EGFR), thereby regulating various biological activities, including cell survival, proliferation, and migration [10][11][12]. The activation of Src causes pulmonary and renal fibrosis [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…These changes serve as mechanical stimuli to activate HSCs at least partially via integrin signaling pathways, forming positive feedback loops [50, 51]. LX-2 cells cultured on acrylamide gels with 12 kPa pressure, mimicking increased tissue stiffness in fibrotic liver, show higher collagen I expression via RHOA upregulation, which is suppressed by c-Src [52]. Primary HSCs cultured in hydrogels stiffened or softening in situ over time revealed time-course dynamic transcriptional changes during the process of culture activation and regression, respectively [53, 54].…”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%
“…When cultured on stiff rather than soft collagen lattices PMF increase their expression of fibrillin-1 [40], and HSC become highly activated loosing their lipid droplets and expressing high levels of α-SMA [41], demonstrating that the stiffness of the matrix has significant functional relevance for the contractile non-parenchymal cells. Interestingly, a recent paper further depicts the underlying mechanisms partly responsible for such activation revealing a negative regulation between RhoA and the cytosolic tyrosine kinase c-SCR [42]. …”
Section: - Sinusoidal Crosstalk In Fibrosis Cirrhosis and Portal Hymentioning
confidence: 99%